Difficulty of the Learners and the Management Measures in Cebuano-Visayan Language as Medium of Instruction - Veloso, Regina; Casinillo, Leomarich F; Hungo, Melbert (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Teachers need help teaching subjects in MTB-MLE and other subjects because the language used is Cebuano. This has an impact on learning activities that could be more optimal. This study aims to analyze the difficulties faced by grade 3 students in implementing Cebuano-Visayan teaching and assess the management actions taken by school administrators and teachers. This research uses a descriptive research design. Data was collected using purposive sampling from 17 school administrators, 30 teachers, and 253 students. Data collection methods use observation and questionnaires. The arithmetic mean is used as a statistical tool. The research results show that school administrators often undertake various management actions to facilitate the implementation of Cebuano-Visayan. Speaking and grammar skills were moderately complex, while reading, comprehension, and vocabulary skills were identified as the most challenging for Grade 3 students. This research revealed that effective and adequate management strategies contribute to the learning difficulties encountered in Cebuano teaching Visayan. Despite efforts by school officials and teachers to address this situation, it continues and even worsens. Therefore, school leaders are advised to re-evaluate their school curricula and thoroughly assess the inclusion of the Cebuano-Visayan language in the lower elementary grades (Grades 1-3) to identify actual problems and provide appropriate interventions and practical solutions.